2007
DOI: 10.1063/1.2813014
|View full text |Cite
|
Sign up to set email alerts
|

Invited Article: An improved double-toroidal spectrometer for gas phase (e,2e) studies

Abstract: A new spectrometer is described for measuring the momentum distributions of scattered electrons arising from electron-atom and electron-molecule ionization experiments. It incorporates and builds on elements from a number of previous designs, namely, a source of polarized electrons and two high-efficiency electrostatic electron energy analyzers. The analyzers each comprise a seven-element retarding-electrostatic lens system, four toroidal-sector electrodes, and a fast position-and-time-sensitive two-dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 56 publications
0
10
0
1
Order By: Relevance
“…This measurement represents a stringent test of theory since there are two active electrons (four-body problem). To date, there have been a limited number of studies reported of the four-body problem for electron-impact excitation-ionization of atoms [10][11][12][13][14] and molecules [4,5,8,9]. For excitationionization of helium, although there was some qualitative shape agreement between experiment and theory, overall the agreement was not very good [5].…”
Section: Introductionmentioning
confidence: 99%
“…This measurement represents a stringent test of theory since there are two active electrons (four-body problem). To date, there have been a limited number of studies reported of the four-body problem for electron-impact excitation-ionization of atoms [10][11][12][13][14] and molecules [4,5,8,9]. For excitationionization of helium, although there was some qualitative shape agreement between experiment and theory, overall the agreement was not very good [5].…”
Section: Introductionmentioning
confidence: 99%
“…Toroidal electron energy spectrometers have been used for many applications that involve the 2 emission of scattered charged particles, including photoemission studies, 3 electron momentum studies, 4 and BSE spectra inside the SEM. 5 These spectrometers typically have first-order focusing properties ͑second-order spherical aberrations͒ in the detection plane.…”
Section: Introductionmentioning
confidence: 99%
“…The improved (e, 2e) binding energy resolution we achieve (2 eV, relative to 7 eV in [12,13]), enabled us to completely resolve transitions to the 2s g and 2p u states from those to the 1s g and 2p u molecular ion states, providing an enhanced level of state selectivity. Figure 2 shows a schematic of the apparatus (see [16]). Light from an 850 nm laser diode is intercepted by a fast acousto-optical shutter, driven at a frequency of 125 kHz by a pulse generator, to produce a train of 2-microsecondduration photon pulses.…”
mentioning
confidence: 99%